Mathematical Discourse : Let the Kids Talk!. - Blanke, Barbara (Professional Resources Ser., 2018)
This resource provides teachers with the tools they need to facilitate mathematical discourse in the 21st century classroom and create opportunities for students to think constructively, communicate effectively, and increase mathematics proficiency.